Kinetika reaksi esterifikasi gliserol dengan asam asetat menggunakan katalisator indion 225 Na - Nuryoto Nuryoto; Hary Sulistyo; Suprihastuti Sri Rahayu; Sutijan Sutijan (Jurnal Rekayasa Proses, 2011)
Biodiesel is an environmentally friendly alternative fuel. The increase of biodiesel production is followed by the increase of the glycerol as by product. Therefore, conversion of glycerol into other products to increase its economic value should be done such as converting it to triacetin. Triacetin is a product from a reaction between glycerol and acetic acid. The use of solid catalysts such as ion exchange resin 225 Indion Na is an alternative method to ease product separation. Preparation of triacetin was conducted in a batch reactor with a stirring speed of 1000 rpm, at temperature of 333 K – 373 K, catalyst diameter of 0.085 cm, the reactant ratio of 7 gmol acetic acid / gmol glycerol, and catalyst concentration of 3% to weight of acetic acid. The sample was taken every 15 minutes in a reaction time of 90 minutes then was analized for free acid concentration. Total acid, free acid, and total glycerol were also determined by volumetric method at the early stage of reaction. The results showed that the highest conversion as high as 41.7% was achieved at 373 K. It was found that the reaction rate was the controlling step. The effect of temperature to rate of reaction constants in the temperature range of 333 K – 373 K can be expressed as follows:kr = 3.344 x 100000 exp (-7,955.56/T ) (1/s)